Tartan tragedy - Fraser, Antonia, 1932- (A Jemima Shore mysery, 2014)
The body of a young man has been found floating in a pool on a remote island in the Scottish Highlands. It just happens to be the island that TV reporter Jemima Shore has rented for a holiday - a holiday that is rapidly falling apart. Confronted with a foreboding stone house, a bitter family feud and cryptic warnings from locals Jemima begins to regret her choice.It is only when another body is found tangled in weeds in the river she begins to realize she has become caught up in something very dark indeed. As she tries to fight her attraction to a suspect, Jemima struggles to work out just who she can trust. In this lonely spot it seems that nobody is quite as they first appear...